The Effect of Ventilation, Heating, Lighting and Bird Density Systems on Chicken Performance Protected Under Molybdenum Conditions - Abio, Abdulwaib Ramadan; Al-Hassi, Samah Hassan Hamad (Al-Mukhtar Journal of Sciences, 2013)
This study was conducted to investigate the effect of ventilation system (fan-window), heating system (gas-kerosene), lighting system (100, 200 and 500 watt) and bird density (8, 10 and 12 bird/m2) on production performance indexes (feed consumption  study was conducted on the broiler houses during the period from February 2009 to Jan 2010 in EL-Bieda-Libya. The results recommended that fan ventilation, gas heating, lighting of 100 watt and bird density of 10 bird/m2 were the most suitable to maximum the feed consumption rate, bird body weight and production index with minimize the feed conversion and the bird mortality.